Economic as a Theoretical Science and Its Relationship to the Historical and Practical Economic Sciences – Part 3 - Menger, Carl (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
In this text, Menger continues his critique of the methodological theses of the German Historical School. For Menger, any exact theoretical approach will be necesarily partial, even in the physical sciences, making it impossible the holistic claim of the Germans. From this point of view the author rejects both the German criticism of the generality of the assumption of self-interest and the imputation of atomism launched against traditional economic theory.